OTOMATISASI PENYIRAMAN TANAMAN BERBASIS IOT DENGAACN SENSOR KELEMBABAN TANAH - Aji Mutakin; Yudi Barnadi; Ase Suryana (Elkom: Jurnal Elektronika dan Komputer, 2025)
Due to the busy activities outside the home, some people do not have time or forget to water their plants, so when they return home they find that the plants have died from drought. Therefore, to overcome this problem by conducting research using Internet of Things technology. The aim of this research is to design an automatic watering tool to overcome manual watering and support learning. This prototype uses a NodeMCU ESP8266 as the main controller, a soil moisture sensor is used to read soil moisture.  Soil moisture sensors are used to detect soil moisture. If the soil humidity is below the minimum limit, the watering process will be active and the watering process will be active if the NodeMCU ESP8266 receives commands from the smartphone.